The Concept of Man in Anthropology-Christian Theology: Answers to Evolutionists - Ferminto Mendrofa; Lastiar Roselyna Sitompul (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
The evolutionist view of humans has a negative influence on education, especially Christian education. Teaching the theory of human evolution in science learning in the classroom makes nature doubtful as God's creation. This is a challenge for Christian educators, for teaching the truth about human nature as the image and likeness of God. Christian educators must be equipped with a Christian theological anthropological understanding of human nature as the image and likeness of God. The purpose of this paper is to answer the evolutionist view of humans in education based on Christian theological anthropological studies. The research method is literature study. The results of the study concluded that humans, both educators and students, were created in the image and likeness of God who has a soul and body with various unique capacities (such as will and knowledge). Humans act as representatives of God on earth who have dominion over the rest of creation and have a special relationship with God as spiritual beings.